Strategi Divisi Humas Dinas Pendidikan DKI Jakarta Dalam Mengelola Sosial Media Instagram @disdikdki - Teuku Nanda Faris Maulana; Sri Wahyuning Astuti (Universitas Telkom, 2024)
This research analyzes the public relations strategies employed by the Jakarta Provincial Department of Education inmanaging the Instagram account @disdikdki to convey messages and information to stakeholders. A qualitative approachwith a case study design was utilized to collect data through interviews and content analysis. The findings reveal theconsistent, accurate, and relevant adoption of strategies in composing content, as well as stringent validation prior toposting. Feedback from stakeholders serves as an evaluative instrument, and recommendations are necessary to maximizethe potential for social media exploration. This research is expected to contribute to the development of public relationsstrategies and to comprehend their effectiveness within the context of educational communication. The study aims to providefurther insights into the role of public relations strategies in the digital era, particularly within the educational institutionenvironment.